Medium aluminum glass as well as preparation method and strengthening method thereof

CN119320234APending Publication Date: 2025-01-17SHANDONG YIXIN PHOTOELECTRIC TECH CO LTD
6 Cites 0 Cited by

Patent Information

Application Number
CN202411310619.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Traditional Chinese aluminum glass is prone to apparent defects, uneven edges, dimensional deviations and concentrated stress during the production process, and is costly and energy-consuming, which affects its application field and optical performance.

Method used

Sodium feldspar, calcite and dolomite powder are used as the main raw materials to control their average particle size to be less than 106μm, and processed through specific proportions and processes, including smelting, annealing and chemical strengthening, to form aluminium glass with high transparency and high mechanical properties. .

Benefits of technology

It reduces the melting temperature and energy consumption of glass, improves the transparency, mechanical strength and chemical stability of glass, reduces surface stress, and enhances the application prospects of glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005050929360000061
    Figure BDA0005050929360000061
  • Figure BDA0005050929360000062
    Figure BDA0005050929360000062
  • Figure BDA0005050929360000071
    Figure BDA0005050929360000071
Patent Text Reader

Abstract

The invention relates to the technical field of glass manufacturing, in particular to medium aluminum glass as well as a preparation method and a strengthening method thereof, and the medium aluminum glass is prepared from the following raw materials in percentage by mass: 40-65% of albite micro powder, 15-35% of calcite micro powder and 5-20% of dolomite micro powder. According to the method for preparing the medium-aluminum glass by adding the albite, the calcite and the dolomite micro powder as the main raw materials, due to the addition of the preparation raw materials, the non-uniform phenomena such as stripes and cloud mist in the glass can be reduced, solid inclusions or wrapped bubbles are reduced, the transparency and appearance quality of the glass are improved, and local component deviation is reduced; the preparation method improves the optical and physical properties of the glass, improves the mechanical strength, chemical stability and thermal stability of the glass, has high compatibility of the preparation raw materials, and has no devitrification tendency in the cooling process of the system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass manufacturing, and in particular to a medium-aluminum glass and a preparation method and a strengthening method thereof. Background Art

[0002] In recent years, with the continuous innovation of display technology, display products have gradually developed towards large screens, flatness, thinness, high definition, energy saving and environmental protection. Flat panel display glass substrates are the core products in the display touch industry. Due to their high investment threshold and high technical requirements, coupled with the long-term strict blockade of core technologies by overseas glass substrate companies, domestic panel companies mainly rely on imports to solve the problem of the source of flat panel display glass substrates.

[0003] The cover is the outermost protective layer of the capacitive touch screen. Since it is in direct contact with the outside world, in addition to the surface finish, thickness and other parameter requirements, high hardness, pressure resistance, scratch resistance and other properties determine the quality of the cover. Compared with other materials, the glass cover (Cover Glass or Cover Lens) has obvious advantages in these important parameters, so it has gradually become the mainstream protection solution for various touch technologies. Generally, the touch module is composed of three parts: the cover, the sensor module, and the LCD panel. At present, the capacitive touch screen solution still has multiple technologies coexisting, and the two major camps of film and glass share the touch market. However, whether it is film (GF, GF2) or glass (GG, OGS), or On-cell and In-cell dominated by Samsung and Apple, the glass cover is an important component.

[0004] When used as a cover plate, although medium-aluminum glass (usually refers to tempered glass containing aluminum oxide or glass that has been specially treated to increase hardness and durability) has good strength and durability, it may still face some technical or application defects. For example, (1) some surface defects such as bubbles, streaks, scratches, spots, etc. may be generated during the production process. The number of these defects is generally required to be controlled at an extremely low level (such as ≤1 / m2), but any visible defects may affect the aesthetics and quality of the cover plate; (2) Although medium-aluminum glass is easy to cut and has high cutting dimensional accuracy, if it is not well controlled, it may still cause uneven edges and dimensional deviations, affecting the assembly accuracy and the sealing and touch of the final product; (3) Although the strengthening treatment improves the pressure and impact resistance of the glass, it may also generate higher stress inside the glass, which may cause spontaneous rupture in extreme cases, especially at the edge or when stress concentration is caused by unreasonable design; (4) The strengthening treatment may have a slight effect on the optical properties of the glass, such as changes in the refractive index, slight visual distortion or color shift, which is a major challenge for high-definition display applications (such as smartphone screens).

[0005] The production of traditional medium-aluminum glass mainly uses chemical raw materials, such as alumina, sodium carbonate, silicon dioxide and soda ash, and the raw material cost is high. In addition, the melting temperature of alumina and silicon dioxide is high, which is the main factor causing the melting temperature to be particularly high, making the energy consumption of producing medium-aluminum glass particularly large, limiting the scale of production and limiting the application field of medium-aluminum glass. At the same time, the development of the electronic information industry has brought about the popularization and popularity of electronic terminals, and the demand for cover glass such as mobile phone tablet screen cover plates and laptop computer screen protection cover plates has become increasingly strong. Traditional cover glass includes medium-aluminum cover glass, which is mainly a lithium aluminum silicon system. However, with the rise of the new energy industry, the price of lithium raw materials has skyrocketed. Based on this, it is necessary to provide a medium-aluminum glass and a preparation method thereof with high transmittance and high mechanical properties and low cost. Summary of the invention

[0006] The first aspect of the present invention provides a medium aluminum glass. The raw materials for preparing the medium aluminum glass include, by mass fraction, 40% to 65% albite powder, 15% to 35% calcite powder, and 5% to 20% dolomite powder.

[0007] Sodium feldspar (NaAlSi 3 O 8 ) is an important framework silicate mineral with a theoretical melting point of 1100°C. It is widely used in glass manufacturing, especially in providing sodium oxide (Na 2 O) plays a key role as a network modifier in the glass network, which helps to lower the melting temperature of the glass and affects its physical properties. Using albite to prepare medium-aluminum glass instead of traditional industrial alumina and silica can not only reduce energy consumption, but also albite resources are abundant and the cost of raw materials is low. Although albite helps to lower the melting point of glass, if its proportion is too high, it may affect the viscosity of the glass, resulting in poor fluidity during the melting process, difficulty in forming a uniform glass body, or increase in melting energy consumption. In addition, albite may induce glass crystallization during the cooling process, especially in the case of rapid cooling or poor temperature control, which will affect the homogeneity and transparency of the glass and lead to the scrapping of the product.

[0008] Calcite crystals have various shapes. It is the main mineral of limestone, marble and beautiful stalactites. Calcite is the most important rock-forming mineral in the earth's crust. It is a carbonate mineral with a chemical composition of CaCO. 3 Calcite decomposes at high temperatures to produce carbon dioxide (CO 3), which not only increases emissions during the production process, but may also form bubbles in the furnace, affecting the transparency and mechanical strength of the glass. Controlling gas release and avoiding bubble defects is a major challenge for the use of calcite. In addition, the calcium oxide produced by the decomposition of calcite may not react uniformly with other components in the glass melt, resulting in local composition deviations, affecting the uniformity and physical properties of the glass. Due to the special reaction kinetics introduced by calcite, more precise temperature control and raw material ratio adjustment are required, which increases the complexity of the production process.

[0009] The main components of dolomite are calcium magnesium carbonate, that is, calcium carbonate and magnesium carbonate. When dolomite is heated to 700-900℃, it decomposes into a mixture of carbon dioxide, calcium oxide and magnesium oxide, called caustic magnesium dolomite, which reacts easily with water. When dolomite is calcined at 1500℃, magnesium oxide becomes periclase, and calcium oxide is transformed into crystalline a-CaO, which has a dense structure, strong water resistance, and a refractoriness of up to 2300℃. The particle size of dolomite has a significant impact on glass production. Uneven particle size distribution or oversized particles may lead to insufficient melting, forming glass stones or other inclusion defects, affecting the transparency and mechanical strength of the glass. Its decomposition and melting behavior may affect the viscosity of the glass melt and the thermodynamic equilibrium during the melting process. It is necessary to accurately control its addition amount and the ratio of other raw materials to maintain good melting performance. Therefore, in the process of glass manufacturing, it is necessary to strictly control and optimize the particle size distribution of dolomite, and make adjustments in the formula and process to ensure the quality and production efficiency of glass products.

[0010] The above three types of ore raw materials have the advantages of low cost and widespread existence in nature, and can be used in large-scale production.

[0011] In some embodiments, the average particle size of the albite powder, calcite powder, and dolomite powder is less than 106 μm.

[0012] The applicant found in the preparation process that the average particle size of albite micropowder, calcite micropowder and dolomite micropowder has a great influence on the quality of medium aluminum glass, especially light transmittance and surface stress. When the average particle size of the above three micropowders is less than 106μm, the micropowder raw materials with uniform particle size are helpful for homogenization of the melt, reducing uneven phenomena such as streaks and clouds in the glass, reducing solid inclusions or encapsulated bubbles, improving the transparency and appearance quality of the glass, reducing local component deviations, and improving the optical and physical properties of the glass. In addition, the average particle size defined by the present invention can increase the surface area, thereby accelerating the decomposition rate and dissolution rate of the micropowder at high temperature, helping to reduce the temperature and time required for melting, and reducing energy consumption.

[0013] In some embodiments, the mass ratio of albite powder, calcite powder, and dolomite powder is (48-62): (25-35): (5.5-20).

[0014] The applicant also found that when the mass ratio of albite powder, calcite powder and dolomite powder is controlled within the above ratio, the transparency and appearance quality of the glass can be further improved, and the optical and physical properties of the glass can be improved.

[0015] In some embodiments, the chemical composition of the sodium feldspar powder is as follows, by weight percentage: SiO 2 :65%~80%,Al 2 O 3 :10%~20%,Na 2 O: 5%~14.8%, K 2 O: 0.1%~4.3%, Fe 2 O 3 :0%~0.7%.

[0016] In some embodiments, the chemical composition of the calcite powder is as follows: CaO: 45% to 60%, MgO: 0.2% to 5%, Al 2 O 3 :0%~2%,Fe 2 O 3 :0%~0.9%.

[0017] In some embodiments, the chemical composition of the dolomite powder is as follows, by weight percentage: CaO: 20% to 35%, MgO: 20% to 25%, SiO 2 :0.5%~2%,Al 2 O 3 :0%~2%,Fe 2 O 3 :0%~0.5%.

[0018] In some embodiments, the medium aluminum glass has a transmittance of 90.1% to 92.8% in the range of 380 nm to 800 nm.

[0019] In some embodiments, the surface stress strength of the medium aluminum glass is 650 MPa to 850 MPa.

[0020] In some embodiments, the ion exchange depth of the medium aluminum glass is 8 μm to 12 μm.

[0021] The second aspect of the present invention provides a method for preparing the above-mentioned medium aluminum glass, comprising the following steps:

[0022] S1. The prepared raw materials are mixed and added to a glass melting furnace, smelted at a temperature of 1550 to 1630 ° C for 4 to 10 hours, and then cooled to 1410 to 1560 ° C for clarification for 1 to 2 hours to obtain a glass liquid;

[0023] S2. The glass liquid is homogenized, and the obtained molded glass is annealed. When the temperature drops to 550-610°C, the temperature is maintained at a constant temperature for 4-8 hours to obtain a precursor glass;

[0024] S3. Heat the precursor glass to 650-850°C for 3-10 hours, and cool it to room temperature to obtain medium aluminum glass.

[0025] The third aspect of the present invention provides a method for strengthening the above-mentioned medium aluminum glass, comprising: placing the medium aluminum glass in a mixed molten salt of molten sodium nitrate and potassium nitrate, and keeping the temperature at 380°C to 450°C for 1 to 5 hours.

[0026] In some embodiments, the mass ratio of sodium nitrate to potassium nitrate is 1:1.

[0027] The applicant found that when sodium nitrate and potassium nitrate are used as reinforcing agents in a mass ratio of 1:1 to strengthen the medium-aluminum glass, the performance of the medium-aluminum glass can be significantly enhanced. It is speculated that this is due to the ion exchange between potassium ions and sodium ions on the surface of the glass. Since the radius of potassium ions is larger than that of sodium ions, potassium ions enter the surface layer of the glass, causing compression of the surface silicate network, thereby forming a layer of high-pressure stress area on the surface of the glass, thereby greatly improving the mechanical strength and impact resistance of the glass.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention provides a method for preparing medium-aluminum glass by adding albite, calcite and dolomite powders of specific particle sizes as main raw materials. By limiting the average particle size of the three to less than 106 μm, the powder raw materials with uniform particle size are helpful for homogenizing the melt, reducing uneven phenomena such as stripes and clouds in the glass, reducing solid inclusions or encapsulated bubbles, improving the transparency and appearance quality of the glass, reducing local component deviations, and improving the optical and physical properties of the glass.

[0030] 2. The present invention provides a medium aluminum glass with high strength, high transmittance and mechanical properties. By adding albite, calcite and dolomite powder, a special proportion of SiO 2 、Al 2 O 3 、Na 2 O, MgO, CaO, Fe 2 O 3In the original three-dimensional silicon-oxygen tetrahedral structure inside the glass, some aluminum ions will replace silicon ions in the silicon-oxygen network to form aluminum-oxygen tetrahedrons or pentahedrons, which changes the connection mode of the glass network, reduces the amount of non-bridging oxygen, and enhances the degree of cross-linking of the network, thereby improving the mechanical strength, chemical stability and thermal stability of the glass. The prepared raw materials are highly compatible with each other, and there is no tendency to crystallize during the cooling process of this system.

[0031] 3. The present invention provides a method for chemically strengthening middle aluminum glass. The surface compressive stress and ion exchange depth of the prepared middle aluminum glass after chemical strengthening treatment are greatly improved. The process is simple, the cost is low, and it has extremely high application prospects. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example

[0034] Example 1-9 provides a medium aluminum glass. The raw materials for preparation are shown in Table 1, wherein the average particle size of albite micropowder, calcite micropowder, and dolomite micropowder is 106 μm; the component content and preparation parameters of the prepared medium aluminum glass are shown in Table 2.

[0035] According to weight percentage, the chemical composition of the sodium feldspar powder is: SiO 2 :65%~80%,Al 2 O 3 :10%~20%,Na 2 O: 5%~14.8%, K 2 O: 0.1%~4.3%, Fe 2 O 3 :0%~0.7%.

[0036] The chemical composition of the calcite powder is as follows: CaO: 45% to 60%, MgO: 0.2% to 5%, Al 2 O 3 :0%~2%,Fe 2 O 3 :0%~0.9%.

[0037] The chemical composition of the dolomite powder is as follows: CaO: 20% to 35%, MgO: 20% to 25%, SiO 2 :0.5%~2%,Al 2O 3 :0%~2%,Fe 2 O 3 :0%~0.5%.

[0038] The preparation method is as follows:

[0039] S1. The prepared raw materials are mixed and added to a glass melting furnace, smelted at a temperature of 1550 to 1630 ° C for 4 to 10 hours, and then cooled to 1500 ± 50 ° C for 2 hours to obtain a glass liquid;

[0040] S2. The glass liquid is homogenized, and the obtained molded glass is annealed. When the temperature drops to 580±20°C, the temperature is maintained constant for 6 hours to obtain a precursor glass;

[0041] S3. Heat the precursor glass to 750±50°C for 8 hours, and cool it to room temperature to obtain medium aluminum glass.

[0042] The prepared medium aluminum glass is strengthened by placing it in a mixed molten salt of molten sodium nitrate and potassium nitrate (mass ratio is 1:1) and keeping it warm at 380°C to 450°C for 1 to 5 hours.

[0043] The transmittance in the wavelength range of 380 to 800 nm was tested using an ultraviolet-visible spectrophotometer in accordance with GB / T40415 standard.

[0044] Using Zheyuan stress meter SLP-2000, referring to standards GB / T18144-2008 and ASTM1422C-99, the surface compressive stress and ion exchange depth of tempered medium aluminum glass were tested.

[0045] Table 1

[0046]

[0047] Table 2

[0048]

[0049] Comparative Example

[0050] Comparative Examples 1-7 provide a medium aluminum glass, and the specific implementation method is the same as Example 1, except that the preparation raw materials are shown in Table 3, and the component content and preparation parameters of the prepared medium aluminum glass are shown in Table 4.

[0051] The preparation method is as follows:

[0052] S1. The prepared raw materials are mixed and added to a glass melting furnace, smelted at a temperature of 1550 to 1630 ° C for 4 to 10 hours, and then cooled to 1500 ± 50 ° C for 2 hours to obtain a glass liquid;

[0053] S2. The glass liquid is homogenized, and the obtained molded glass is annealed. When the temperature drops to 580±20°C, the temperature is maintained constant for 6 hours to obtain a precursor glass;

[0054] S3. Heat the precursor glass to 750±50°C for 8 hours, and cool it to room temperature to obtain medium aluminum glass.

[0055] The prepared medium aluminum glass is strengthened by placing it in a mixed molten salt of molten sodium nitrate and potassium nitrate (mass ratio is 1:1) and keeping it warm at 380°C to 450°C for 1 to 5 hours.

[0056] The transmittance in the wavelength range of 380 to 800 nm was tested using an ultraviolet-visible spectrophotometer in accordance with GB / T40415 standard.

[0057] Using Zheyuan stress meter SLP-2000, referring to standards GB / T18144-2008 and ASTM1422C-99, the surface compressive stress and ion exchange depth of tempered medium aluminum glass were tested.

[0058] Table 3

[0059] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Sodium feldspar 65.02 74.32 32.07 50.32 67.25 46.32 49.39 Calcite 28.39 22.32 18.22 31.82 26.19 37.27 28.78 dolomite 6.59 3.36 50.29 17.86 6.56 16.41 21.83

[0060] Table 4

[0061]

[0062]

[0063] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A medium aluminum glass, characterized in that: Calculated by mass fraction, the raw materials for preparing the medium aluminum glass include: 40% to 65% albite powder, 15% to 35% calcite powder, and 5% to 20% dolomite powder.

2. The aluminum glass according to claim 1, characterized in that: The average particle sizes of the albite micropowder, calcite micropowder and dolomite micropowder are all less than 106 μm.

3. The aluminum-based glass according to claim 2, characterized in that: Calculated by weight percentage, the chemical composition of the albite powder is: SiO2: 65% to 80%, Al2O3: 10% to 20%, Na2O: 5% to 14.8%, K2O: 0.1% to 4.3%, and Fe2O3: 0% to 0.7%.

4. The medium aluminum glass according to claim 3, characterized in that: Calculated by weight percentage, the chemical composition of the calcite powder is: CaO: 45% to 60%, MgO: 0.2% to 5%, Al2O3: 0% to 2%, and Fe2O3: 0% to 0.9%.

5. The medium aluminum glass according to claim 4, characterized in that: Calculated by weight percentage, the chemical composition of the dolomite powder is: CaO: 20% to 35%, MgO: 20% to 25%, SiO2: 0.5% to 2%, Al2O3: 0% to 2%, and Fe2O3: 0% to 0.5%.

6. The medium aluminum glass according to claim 5, characterized in that: The transmittance of the medium aluminum glass is 90.1% to 92.8% within the range of 380nm to 800nm.

7. The aluminum-based glass according to claim 6, characterized in that: The surface stress intensity of the medium aluminum glass is 650MPa to 850MPa.

8. The medium aluminum glass according to claim 7, characterized in that: The ion exchange depth of the medium aluminum glass is 8 μm to 12 μm.

9. A method for preparing the medium aluminum glass according to any one of claims 1 to 8, characterized in that: The steps include: S1. The prepared raw materials are mixed and added to a glass melting furnace, smelted at a temperature of 1550 to 1630 ° C for 4 to 10 hours, and then cooled to 1410 to 1560 ° C for clarification for 1 to 2 hours to obtain a glass liquid; S2. The glass liquid is homogenized, and the obtained molded glass is annealed. When the temperature drops to 550-610°C, the temperature is maintained at a constant temperature for 4-8 hours to obtain a precursor glass; S3. Heat the precursor glass to 650-850°C for 3-10 hours, and cool it to room temperature to obtain medium aluminum glass.

10. A method for strengthening the medium aluminum glass according to any one of claims 1 to 8, characterized in that: include: The medium aluminum glass is placed in a mixed molten salt of molten sodium nitrate and potassium nitrate and kept warm at 380° C. to 450° C. for 1 to 5 hours.

Citation Information

Patent Citations

  • Method for reducing microbubbles of alumina silicate glass

    CN103395984A

  • Alumina silicate glass and preparation method thereof as well as cover plate and display device

    CN109437555A

  • High-transmittance medium-aluminum glass with increased depth of layer

    CN109796130A

  • Medium aluminum glass as well as preparation method and application thereof

    CN116514391A

  • Ultra-white medium aluminum glass and composition and preparation method thereof

    CN116854365A